Post-Pandemic 'Bleisure' Trend in Indonesia: Literature Review Regarding Lifestyle Changes and Implications for the Tourism Industry and Employment - Rahjasa, Putu Surya Laksana (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article examines the growing trend of Bleisure—blending business and leisure travel—in Indonesia post-pandemic, analysing its impact on work patterns, the tourism industry, and employee well-being. The study highlights how the increased flexibility in work arrangements and the rising need for work-life balance have driven the adoption of Bleisure among professionals. Grounded in Work-Life Balance Theory (Greenhaus & Beutell, 1985), Motivation-Hygiene Theory (Herzberg, 1959), and Organizational Change Theory (Lewin, 1951), the research explores both the benefits and challenges of Bleisure. The findings suggest that while Bleisure enhances job satisfaction and work-life integration, it also poses risks such as burnout and unequal access among employees. Furthermore, the impact on the tourism industry is significant, with changes in travel duration and spending patterns. The study concludes that effective management and supportive policies are essential for maximizing the positive effects of Bleisure on both employees and the tourism sector.